The role of human development and governance on eradication of poverty / Mohd Haziq Jomrah @ Osman - Jomrah @ Osman, Mohd Haziq (2020)
To the best of my knowledge, the human development index and governance influence on poverty in Asia has never been investigated. Data retrieved through World Bank Data and Human Development Report provide a unique opportunity for studying the roles of the human development index and governance on poverty, given significant increases in the human development index while having inconsistent governance recent years. This article examines the roles of the human development index and governance on the incidence of poverty and the transitions into and out of poverty in Asia using data from the World Bank Data, Human Development Report from 2009 to 2018. The results indicate that the human development index and governance had poverty-reducing effects and negative relationship.